2009
DOI: 10.1111/j.1537-2995.2009.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell alloimmunization in sickle cell disease patients in Uganda

Abstract: The rate of RBC alloimmunization in Ugandan SCD patients was 6.1%. The homogeneity between donors and SCD patients plus the low transfusion load may explain this immunization frequency. Nevertheless, our study confirms the significance of RBC alloimmunization as a complication in Ugandan SCD patients. Therefore, there is need to improve immunohematologic testing in Uganda so that RBC alloimmunization and its consequences may be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
2
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(125 citation statements)
references
References 32 publications
10
104
2
9
Order By: Relevance
“…In a study of Ugandan patients with SCD, 6.1% were alloimmunized despite low transfusion exposure and ethnic similarity between donors and recipients. 57 Our recent study evaluating the effect of C-, E-, and K- …”
Section: Strategies To Prevent Alloimmunization Rbc Antigen-matching mentioning
confidence: 99%
“…In a study of Ugandan patients with SCD, 6.1% were alloimmunized despite low transfusion exposure and ethnic similarity between donors and recipients. 57 Our recent study evaluating the effect of C-, E-, and K- …”
Section: Strategies To Prevent Alloimmunization Rbc Antigen-matching mentioning
confidence: 99%
“…The authors explained that since blood cannot be collected locally, use of blood mostly from French Caucasian blood donors is causing alloimmunization in the Guianese population due to ethnic/geneticdifferences 13 . Natukunda et al 6 reported that the rate of RBC alloimmunization in Ugandan SCD patients was 6.1%. The homogeneity between donors and SCD patients plus the low transfusion load may explain this low immunization frequency 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Natukunda et al 6 reported that the rate of RBC alloimmunization in Ugandan SCD patients was 6.1%. The homogeneity between donors and SCD patients plus the low transfusion load may explain this low immunization frequency 6 . Chou et al 3 found alloimmunization prevalence as %58 among the patients who undergo chronic transfusion, 15% among the patients who undergo episodic transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations